Paediatric hyperthermia-related deaths while entrapped and unattended inside vehicles: The Canadian experience and anticipatory guidance for prevention. Issue 3 (16th July 2019) - Ho, Karen; Minhas, Ripudaman; Young, Elizabeth; Sgro, Michael; Huber, Joelene F
Abstract: An average of 37 children die of hyperthermia inside parked vehicles annually in the USA. The majority of cases are due to a caregiver forgetting them (~55%), while ~13% are due to intentionally leaving children unattended and ~28% occur when children climb into unlocked vehicles. The cause of four per cent is unknown. There are no published data on incidence in Canada. Through information provided from provincial and territorial coroner's offices, Canadian government agencies and media reports, six cases of vehicular hyperthermia deaths were confirmed since 2013. Three were attributed to children left unintentionally in vehicles; one occurred after a child climbed into an unlocked vehicle and two cases are undetermined. Attention or memory lapses are hypothesized to occur due to distraction, stress, fatigue, or routine changes. Educating caregivers about the dangers of leaving children in vehicles and providing preventative strategies through anticipatory guidance may reduce these tragedies (see graphic abstract).